Mobile health technology for remote home monitoring after surgery: a meta-analysis. Issue 11 (18th October 2021) - Dawes, A J; Lin, A Y; Varghese, C; Russell, M M; Lin, A Y
Abstract: Background: Mobile health (mHealth) technology has been proposed as a method of improving post-discharge surveillance. Little is known about how mHealth has been used to track patients after surgery and whether its use is associated with differences in postoperative recovery. Methods: Three databases (PubMed, MEDLINE and the Cochrane Central Registry of Controlled Trials) were searched to identify studies published between January 1999 and February 2021. Mobile health was defined as any smartphone or tablet computer capable of electronically capturing health-related patient information and transmitting these data to the clinical team. Comparable outcomes were pooled via meta-analysis with additional studies compiled via narrative review. The quality of each study was assessed based on Grading of Recommendations Assessment, Development, and Evaluation (GRADE) criteria. Results: Forty-five articles met inclusion criteria. While the majority of devices were designed to capture general health information, others were specifically adapted to the expected outcomes or potential complications of the index procedure. Exposure to mHealth was associated with fewer emergency department visits (odds ratio 0.42, 95 per cent c.i. 0.23 to 0.79) and readmissions (odds ratio 0.47, 95 per cent c.i. 0.29 to 0.77) as well as accelerated improvements in quality of life after surgery. There were limited data on other postoperative outcomes. Conclusion: Remote home monitoring via mHealth is feasible, adaptable, and may even promote more effective postoperative care. Given the rapid expansion of mHealth, physicians and policymakers need to understand these technologies better so that they can be integrated into high-quality clinical care. Abstract : The authors performed a systematic review to determine how mobile health (mHealth) technology is being used to track surgical patients after discharge and whether this type of monitoring is associated with differences in postoperative outcomes. They found that remote home monitoring via mHealth is feasible and flexible for a variety of patients and surgical teams. Use of mHealth also appears to be associated with a reduction in both emergency department visits and hospital readmissions as well as accelerated improvements in quality of life. Lay Summary: A systematic review was performed to determine how mobile health (mHealth) technology is being used to track surgical patients after hospital discharge, and whether exposure to mHealth is associated with differences in postoperative recovery. Remote home monitoring via mHealth is feasible and flexible enough to meet the demands of a variety of patients and clinical teams. Exposure to mHealth also appears to be associated with a reduction in both emergency department visits and hospital readmissions as well as accelerated improvements in quality of life. mHealth represents an important next step in postoperative surveillance, although better performance data, targeted incentives and clearer guidelines are still needed.